Genomic alterations and molecular subtypes of gastric cancers in Asians. Issue 1 (9th May 2016) - Ye, Xiang S.; Yu, Chunping; Aggarwal, Amit; Reinhard, Christoph
Abstract: Gastric cancer (GC) is a highly heterogenic disease, and it is the second leading cause of cancer death in the world. Common chemotherapies are not very effective for GC, which often presents as an advanced or metastatic disease at diagnosis. Treatment options are limited, and the prognosis for advanced GCs is poor. The landscape of genomic alterations in GCs has recently been characterized by several international cancer genome programs, including studies that focused exclusively on GCs in Asians. These studies identified major recurrent driver mutations and provided new insights into the mutational heterogeneity and genetic profiles of GCs. An analysis of gene expression data by the Asian Cancer Research Group (ACRG) further uncovered four distinct molecular subtypes with well‐defined clinical features and their intersections with actionable genetic alterations to which targeted therapeutic agents are either already available or under clinical development. In this article, we review the ACRG GC project. We also discuss the implications of the genetic and molecular findings from various GC genomic studies with respect to developing more precise diagnoses and treatment approaches for GCs.